Adhesive, adhesive sheet, laminate and display

The adhesive composition addresses the challenges of flexibility and durability in foldable and rollable displays by using a specific blend of acrylic copolymer, monomers, and catalysts, ensuring excellent performance in extreme conditions and maintaining display quality.

JP2025007130APending Publication Date: 2025-01-17TOYO INK MFG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023108325
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Conventional adhesives fail to meet the requirements of flexibility, heat resistance, and humidity resistance necessary for foldable and rollable displays, particularly in extreme temperature and humidity conditions, and cannot simultaneously satisfy dynamic and static flexibility and windability.

Method used

An adhesive composition comprising an acrylic copolymer, polyfunctional and monofunctional (meth)acrylate monomers, organic peroxide, and a reducing agent, with specific components and ratios to achieve rapid curing and improved flexibility, heat resistance, and humidity resistance, including a redox catalyst system for efficient polymerization at room temperature.

Benefits of technology

The adhesive composition provides excellent transparency, heat resistance, humidity resistance, flexibility, and windability, with fast curing properties, maintaining performance over time and enhancing display visibility and contrast.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007130000001_ABST
    Figure 2025007130000001_ABST
Patent Text Reader

Abstract

To provide an adhesive, an adhesive sheet and a laminate thereof as well as a display having excellent transparency, heat resistance and moist heat resistance and capable of achieving both flexibility and winding properties.SOLUTION: There is provided an adhesive which contains a specific acrylic copolymer (A), a multifunctional (meth)acrylate monomer (B), a monofunctional (meth)acrylate monomer (C), an organic peroxide (D) and a reducing agent (E), wherein the one minute half-life temperature of the organic peroxide (D) is 90 to 135°C, the reducing agent (E) contains one or more selected from the group consisting of a tertiary amine, a thiourea derivative and a transition metal salt and the adhesive contains 0.5 to 3 pts.wt. of the organic peroxide (D) and 0.005 to 0.5 pt.wt of the reducing agent (E) based on total 100 pts.mass of the acrylic copolymer (A), the multifunctional (meth)acrylate monomer (B) and the monofunctional (meth)acrylate monomer (C).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-sensitive adhesive for forming a laminate including a light-transmitting substrate, a pressure-sensitive adhesive layer, and a polarizing plate, a pressure-sensitive adhesive sheet, and a laminate having a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive sheet. The laminate is used for a display. [Background technology]

[0002] Thin image display devices such as liquid crystal displays and organic EL displays usually have a laminated structure including image forming layers such as a liquid crystal layer and an organic EL layer, and an optical film and a cover panel. Adhesives are generally used to bond each layer constituting an image display device. For example, a transparent conductive film used in a touch panel is laminated on a member such as a support glass or a support film via an adhesive layer. In addition, a polarizing plate film used in an image device is attached to a liquid crystal module or an organic EL module via an adhesive layer. In this way, each member of the image display device is attached and fixed by the adhesive layer.

[0003] Furthermore, while flat displays using glass substrates have been mainstream as the image display devices, flexible displays using flexible substrates such as plastics, such as foldable displays and rollable displays, have been developed in recent years. Such flexible displays have various advantages, such as being lighter, thinner, more flexible, and more attractive in design, compared to conventional flat displays using glass substrates.

[0004] The adhesive layer has traditionally been required to have a property of not foaming or peeling in a high temperature environment or a high temperature and high humidity environment, but in recent years, further functionality has been required, and flexibility has become necessary for flexible displays. For example, in the case of a foldable display, flexibility is the suitability (flexibility) of the display to bend. In general, the flexibility requires a property (dynamic flexibility) that does not cause foaming, lifting, or peeling when repeatedly folded.

[0005] On the other hand, since a curing process is necessary in the manufacturing process of a general adhesive layer, the development of fast-curing adhesives is being promoted for the purpose of shortening the process and reducing costs. In addition, the thickness of the adhesive layer used in a foldable display is generally 50 to 200 μm, which is a thick film, and the coating film defects during roll winding after coating due to the insufficient hardness of the adhesive layer, and orange peel and dents (dents) that occur during the curing process can become problems, so that an adhesive that can shorten the curing process is suitable for suppressing such coating defects.

[0006] Patent Document 1 discloses a pressure-sensitive adhesive containing a base polymer and an oligomer, while Patent Document 2 discloses an ultraviolet-curable pressure-sensitive adhesive made of a urethane acrylate and an acrylic monomer. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2023-47037 A [Patent Document 2] JP 2023-70690 A Summary of the Invention [Problem to be solved by the invention]

[0008] In recent years, in order to meet the demands of displays with even higher durability, adhesives used are required to have higher durability than ever before. In particular, for foldable displays, in addition to the property of not causing foaming, lifting, or peeling when repeatedly bent (dynamic flexibility), it is also necessary to have the property of not causing foaming, lifting, or peeling when the bent state is maintained for a long time (static flexibility). In addition, for rollable displays, suitability for winding up the display (winding ability) is required so that it can be used for rollable displays. For winding ability, the property of not causing foaming, lifting, or peeling when the rolled state is maintained for a long time is required.

[0009] Furthermore, while conventionally, this flexibility was a required quality only at room temperature, with the spread of displays, flexibility in low-temperature environments such as those in extremely cold regions, and high-temperature environments such as those found in extremely hot regions or inside automobiles under the blazing sun, is now also becoming necessary.

[0010] In contrast, conventional pressure-sensitive adhesive sheets currently fail to satisfy the requirements for heat resistance, moist heat resistance, and flexibility, such as bendability and rollability, at a level that is practically problem-free. In addition, flexibility requires dynamic bending, static bending, and rollability depending on the display configuration. Although it is possible to satisfy these flexibility requirements individually, it is difficult to satisfy all of them at the same time. In addition, the current situation is that dynamic bending, static bending, and rollability cannot be satisfied in high temperature environments or high temperature and high humidity environments.

[0011] An object of the present invention is to provide a pressure-sensitive adhesive, a pressure-sensitive adhesive sheet, and a laminate thereof, which are excellent in transparency, and further have satisfactory heat resistance, moist heat resistance, bending property and winding property, and which have fast curing properties and do not deteriorate over time, as well as a display. [Means for solving the problem]

[0012] As a result of extensive research, the present inventors have found that the problems of the present invention can be solved in the following manner. Based on this finding, the present invention has been completed. That is, an embodiment of the present invention includes an acrylic copolymer (A), a polyfunctional (meth)acrylate monomer (B), a monofunctional (meth)acrylate monomer (C), an organic peroxide (D), and a reducing agent (E), The problem is solved by a pressure-sensitive adhesive characterized in that the acrylic copolymer (A) is a copolymer of a monomer mixture containing a (meth)acrylic acid alkyl ester monomer (a-1) having an alkyl group with 8 to 12 carbon atoms, and a monomer (a-2) having a hydroxyl group and / or a monomer (a-3) having a carboxyl group, the organic peroxide (D) has a 1-minute half-life temperature of 90 to 135°C, and the reducing agent (E) contains one or more selected from the group consisting of tertiary amines, thiourea derivatives, and transition metal salts, and the adhesive contains 0.5 to 3 parts by mass of the organic peroxide (D) and 0.005 to 0.5 parts by mass of the reducing agent (E) per 100 parts by mass in total of the acrylic copolymer (A), the polyfunctional (meth)acrylate monomer (B), and the monofunctional (meth)acrylate monomer (C).

[0013] Another embodiment of the present invention is the above-mentioned pressure-sensitive adhesive, characterized in that the monofunctional (meth)acrylate monomer (C) comprises one or more monomers selected from the group consisting of aromatic (meth)acrylate monomers, aliphatic cyclic (meth)acrylate monomers, and (meth)acrylate monomers having an amide group.

[0014] Another embodiment of the present invention is the above pressure-sensitive adhesive, characterized in that it contains 1 to 40 parts by mass of a polyfunctional (meth)acrylate monomer (B) and 1 to 60 parts by mass of a monofunctional (meth)acrylate monomer (C) per 100 parts by mass of the acrylic copolymer (A).

[0015] Another embodiment of the present invention is the pressure-sensitive adhesive described above, which satisfies all of the following (1) to (3). (1) The storage modulus of the adhesive at 0°C and 1 Hz is 1×10 5 ~1×10 6 Pa (2) The storage modulus of the adhesive at 150°C and 1 Hz is 1×10 4 ~1×105 Pa (3) The peak top temperature of the loss factor of the adhesive at 1 Hz is -45 to -10°C.

[0016] Another embodiment of the present invention is a pressure-sensitive adhesive sheet in which a pressure-sensitive adhesive layer, which is a cured product of the pressure-sensitive adhesive, is sandwiched between release films.

[0017] Moreover, an embodiment of the present invention is a laminate comprising a light-transmitting substrate, a pressure-sensitive adhesive layer, and a polarizing plate, the pressure-sensitive adhesive layer being a cured product of the pressure-sensitive adhesive.

[0018] Another embodiment of the present invention is a display comprising the laminate and an optical element. Effect of the Invention

[0019] The present invention provides an adhesive and an adhesive sheet that are excellent in transparency, and further have satisfactory heat resistance, moist heat resistance, bending property and winding property, and are fast curing and do not deteriorate over time, as well as a laminate using the adhesive sheet. Furthermore, by using the pressure-sensitive adhesive sheet and laminate of the present invention, a display excellent in visibility and contrast can be provided. [Brief description of the drawings]

[0020] [Figure 1] 1 is a schematic cross-sectional view partially illustrating a pressure-sensitive adhesive sheet of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view partially illustrating a laminate, which is an example of use of the pressure-sensitive adhesive sheet of the present invention. [Diagram 3] FIG. 1 is a schematic cross-sectional view partially illustrating a display, which is an example of the use of the pressure-sensitive adhesive sheet of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Hereinafter, examples of the configurations of the pressure-sensitive adhesive, pressure-sensitive adhesive sheet, laminate, and display of the present invention will be described, but the present invention is not limited thereto.

[0022] The terms used in this specification are defined. An acrylic copolymer is a copolymer obtained by copolymerizing a monomer mixture, the essential component of which is a compound having a (meth)acryloyl group in the molecule, by a radical reaction. A polyfunctional (meth)acrylate monomer is a monomer having two or more (meth)acryloyl groups in the molecule. A monofunctional (meth)acrylate monomer is a monomer having one (meth)acryloyl group in the molecule. In addition, a (meth)acrylate monomer includes an acrylate monomer and a methacrylate monomer, and is a synonym of a (meth)acrylic acid ester monomer. In the present invention, a sheet, a film, and a tape are synonymous. In this specification, the acrylic copolymer (A), the polyfunctional (meth)acrylate monomer (B), the monofunctional (meth)acrylate monomer (C), the (meth)acrylic acid alkyl ester monomer (a-1) having an alkyl group with a carbon number of 8 to 12, the monomer (a-2) having a hydroxyl group, the monomer (a-3) having a carboxyl group, and the other monomer (a-4) other than (a-1) to (a-3) may be abbreviated as copolymer (A), monomer (B), monomer (C), monomer (a-1), monomer (a-2), monomer (a-3), and monomer (a-4), respectively. Unless otherwise noted, the various components appearing in this specification may be used independently as a single type or as a combination of two or more types.

[0023] In this specification, any numerical range specified using "to" is intended to include the numerical values ​​before and after "to" as the lower and upper limit values ​​of the range.

[0024] "Adhesive" The adhesive of the present invention comprises an acrylic copolymer (A), a polyfunctional (meth)acrylate monomer (B), a monofunctional (meth)acrylate monomer (C), an organic peroxide (D) and a reducing agent (E), the acrylic copolymer (A) being a copolymer of a monomer mixture comprising a (meth)acrylic acid alkyl ester monomer (a-1) having an alkyl group with a carbon number of 8 to 12, and a monomer (a-2) having a hydroxyl group and / or a monomer (a-3) having a carboxyl group, the organic peroxide (D) having a one-minute half-life temperature of 90 to 135°C, the reducing agent (E) comprising one or more selected from the group consisting of tertiary amines, thiourea derivatives and transition metal salts, and the adhesive is characterized in that the adhesive comprises 0.5 to 3 parts by weight of the organic peroxide (D) and 0.005 to 0.5 parts by weight of the reducing agent (E) per 100 parts by mass of the acrylic copolymer (A). In the pressure-sensitive adhesive of the present invention, the organic peroxide (D) is used for the purpose of functioning as a polymerization initiator. The reducing agent (E) is used for the purpose of forming a redox catalyst system together with the organic peroxide (D). The formation of a redox catalyst system by both of them can rapidly promote the decomposition of the organic peroxide (D), and the polymerization of the polyfunctional (meth)acrylate monomer (B) and the monofunctional (meth)acrylate monomer (C) can proceed even at room temperature.

[0025] <Acrylic copolymer (A)> The acrylic copolymer (A) is a copolymer of a monomer mixture containing a (meth)acrylic acid alkyl ester monomer (a-1) having an alkyl group with a carbon number of 8 to 12, and a monomer (a-2) having a hydroxyl group and / or a monomer (a-3) having a carboxyl group. The monomer mixture may contain a monomer (a-4) described below as necessary.

[0026] [Monomer (a-1)] Monomer (a-1) is a (meth)acrylic acid alkyl ester monomer having an alkyl group having 8 to 12 carbon atoms in the molecule, and specific examples thereof include 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, and dodecyl (meth)acrylate. By including the monomer (a-1), the stress relaxation property of the pressure-sensitive adhesive is improved, a flexible pressure-sensitive adhesive layer is obtained, and flexibility can be improved. Of these monomers (a-1), 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, and dodecyl (meth)acrylate are preferred from the viewpoints of adhesion to substrates and flexibility.

[0027] The monomer (a-1) is preferably contained in an amount of 5 to 99% by mass, more preferably 20 to 90% by mass, based on 100% by mass of the monomer mixture. A content of 5% by mass or more makes it easier to obtain sufficient flexibility. A content of 99% by mass or less is also preferable because it makes it easier to achieve both cohesive strength and flexibility.

[0028] [Monomer (a-2)] Monomer (a-2) is a monomer having a hydroxyl group in the molecule, and specific examples thereof include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, allyl alcohol, and 3-butene-1-ol. By including the monomer (a-2), the cohesive strength of the pressure-sensitive adhesive is improved, a tough pressure-sensitive adhesive layer is obtained, and the adhesive strength can be improved. Of these, 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are preferred from the viewpoints of cohesive strength and adhesive strength.

[0029] The monomer (a-2) is preferably contained in an amount of 1 to 40% by mass, more preferably 2 to 30% by mass, based on 100% by mass of the monomer mixture. A content of 1% by mass or more makes it easier to obtain sufficient cohesive strength. A content of 40% by mass or less is also preferable because it makes it easier to achieve both cohesive strength and flexibility.

[0030] [Monomer (a-3)] Monomer (a-3) is a monomer having a carboxyl group in the molecule, and specific examples thereof include (meth)acrylic acid, p-carboxybenzyl acrylate, β-carboxyethyl acrylate, maleic acid, monoethyl maleic acid, itaconic acid, citraconic acid, and fumaric acid. By including the monomer (a-3), the cohesive strength of the pressure-sensitive adhesive is improved, a tough pressure-sensitive adhesive layer is obtained, and the adhesive strength can be improved. Of these, (meth)acrylic acid is preferred from the viewpoints of cohesive strength and adhesive strength.

[0031] The monomer (a-3) is preferably contained in an amount of 0.2 to 5 mass %, more preferably 0.4 to 2 mass %, based on 100 mass % of the monomer mixture. A content of 0.2 mass % or more makes it easier to obtain sufficient cohesive strength. A content of 5 mass % or less is also preferable because it makes it easier to achieve both cohesive strength and stress relaxation properties.

[0032] [Monomer (a-4)] The monomer (a-4) is a monomer other than the monomers (a-1) to (a-3), and the acrylic copolymer (A) may further contain the monomer (a-4) in addition to the monomers (a-1) to (a-3). Examples of the monomer (a-4) include (meth)acrylic acid alkyl ester monomers other than the monomer (a-1), aliphatic cyclic (meth)acrylate monomers, aromatic (meth)acrylate monomers, (meth)acrylic acid monomers having an epoxy group, (meth)acrylic acid monomers having an amino group, monomers having an alkyleneoxy group, monomers having an amide group, and vinyl monomers.

[0033] Specific examples of (meth)acrylic acid alkyl ester monomers other than (a-1) include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, isohexyl (meth)acrylate, and heptyl (meth)acrylate.

[0034] Specific examples of the aliphatic cyclic (meth)acrylate monomer include isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, cyclododecyl (meth)acrylate, methylcyclohexyl (meth)acrylate, and trimethylcyclohexyl (meth)acrylate.

[0035] Specific examples of the aromatic (meth)acrylate monomer include benzyl (meth)acrylate, phenyl (meth)acrylate, o-phenylphenol (meth)acrylate, phenoxy (meth)acrylate, pt-butylphenyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxypropyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, ethylene oxide-modified phenol (meth)acrylate (e.g., M-101A and M-102, both manufactured by Toagosei Co., Ltd.), ... and ethylene oxide-modified phenol (meth)acrylate (e.g., M-102, both manufactured by Toagosei Co., Ltd.). oxide-modified nonylphenol (meth)acrylate (e.g., M-111, M-113, both manufactured by Toagosei Co., Ltd.), 2-hydroxy-3-phenoxypropyl (meth)acrylate, methoxybenzyl (meth)acrylate, chlorobenzyl (meth)acrylate, cresyl (meth)acrylate, polystyryl (meth)acrylate, 2-naphthoethyl (meth)acrylate, 2-naphthoxyethyl acrylate, 2-(4-methoxy-1-naphthoxy)ethyl (meth)acrylate, biphenyl (meth)acrylate, and the like.

[0036] Specific examples of the (meth)acrylic acid monomer having an epoxy group include glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, and 6-methyl-3,4-epoxycyclohexylmethyl (meth)acrylate.

[0037] Specific examples of the (meth)acrylic acid monomer having an amino group include monomethylaminoethyl (meth)acrylate, monoethylaminoethyl (meth)acrylate, monomethylaminopropyl (meth)acrylate, and monoethylaminopropyl (meth)acrylate.

[0038] Specific examples of the monomer having an alkyleneoxy group include the monomer represented by the following general formula (1) and the monomer represented by the following general formula (2).

[0039] [ka] General formula (1)

[0040] [ka] General formula (2)

[0041] In general formula (1) and general formula (2), R1 and R2 each independently represent a hydrogen atom or a methyl group, n and m each represent an integer representing a repeating unit, and 1≦n≦25, 1≦m≦25, and preferably 1≦n≦13, 1≦m≦5.

[0042] Commercially available products of the monomer represented by the general formula (1) include, for example, methoxyethyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd.: in the above formula (1), R1 is a hydrogen atom, n=1), methoxydiethylene glycol acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd.: in the above formula (1), R1 is a hydrogen atom, n=2), methoxytriethylene glycol acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd.: in the above formula (1), R1 is a hydrogen atom, n=3), methoxypolyethylene glycol #400 acrylate (manufactured by Shin-Nakamura Chemical Co., Ltd.: in the above formula (1), R1 is a hydrogen atom, n=9), methoxypolyethylene glycol #600 acrylate (manufactured by Shin-Nakamura Chemical Co., Ltd.: in the above formula (1), R1 is a hydrogen atom, n=13), and methoxypolyethylene glycol #1000 acrylate (manufactured by Shin-Nakamura Chemical Co., Ltd.: in the above formula (1), R1 is a hydrogen atom, n=2). 3), methoxydiethylene glycol methacrylate (Shin-Nakamura Chemical Co., Ltd.: in the above formula (1), R1 is a methyl group, n=2), methoxytriethylene glycol methacrylate (Shin-Nakamura Chemical Co., Ltd.: in the above formula (1), R1 is a methyl group, n=3), methoxytetraethylene glycol methacrylate (Shin-Nakamura Chemical Co., Ltd.: in the above formula (1), R1 is a methyl group, n=4), methoxypolyethylene glycol #400 methacrylate (Shin-Nakamura Chemical Co., Ltd.: in the above formula (1), R1 is a hydrogen atom, n=9), methoxypolyethylene glycol #600 methacrylate (Shin-Nakamura Chemical Co., Ltd.: in the above formula (1), R1 is a hydrogen atom, n=13), and methoxypolyethylene glycol #1000 methacrylate (Shin-Nakamura Chemical Co., Ltd.: in the above formula (1), R1 is a hydrogen atom, n=23).

[0043] Commercially available products of the monomer represented by the general formula (2) include, for example, methoxytripropyleneglycol acrylate (manufactured by Shin-Nakamura Chemical Co., Ltd.: in the above formula (2), R1 is a hydrogen atom, m=3) and methoxytripropyleneglycol methacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd.: in the above formula (2), R1 is a methyl group, m=3).

[0044] Specific examples of monomers having an amide group include N-methylacrylamide, N-isopropylacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, N,N-dimethylaminopropyl(meth)acrylamide, diacetone acrylamide, N-(butoxymethyl)acrylamide, N-hydroxyethylacrylamide, N-vinylpyrrolidone, N-vinylcaprolactam, and acryloylmorpholine.

[0045] Specific examples of the vinyl monomer include vinyl acetate, vinyl crotonate, styrene, and acrylonitrile.

[0046] The monomer (a-4) is preferably contained in an amount of 4 to 80 mass%, more preferably 4 to 50 mass%, based on 100 mass% of the monomer mixture. A content of 4 mass% or more makes it easier to obtain sufficient cohesive strength. Also, a content of 80 mass% or less is preferable because it makes it easier to achieve both cohesive strength and stress relaxation properties.

[0047] These monomers (a-1) to (a-4) can each be used independently alone or in combination of two or more kinds.

[0048] [Production of acrylic copolymer (A)] The copolymer (A) can be produced by polymerizing a monomer mixture containing (a-1) a (meth)acrylic acid alkyl ester monomer having an alkyl group of 8 to 12 carbon atoms, (a-2) a monomer having a hydroxyl group, and / or (a-3) a monomer having a carboxyl group. The polymerization can be carried out by a known polymerization method such as solution polymerization, bulk polymerization, emulsion polymerization, suspension polymerization, etc., but solution polymerization or bulk polymerization is preferred. The solvent used in the solution polymerization is preferably, for example, acetone, methyl acetate, ethyl acetate, toluene, xylene, anisole, methyl ethyl ketone, cyclohexanone, etc. In the case of solution polymerization, the polymerization temperature is preferably 60 to 120° C. The polymerization time is preferably about 5 to 12 hours. In the case of bulk polymerization, the polymerization temperature is preferably 40 to 80° C. The polymerization time is preferably about 3 to 8 hours.

[0049] The polymerization initiator used in the polymerization is preferably a radical polymerization initiator, and the radical polymerization initiator is generally a peroxide or an azo compound. Examples of peroxides include dialkyl peroxides such as di-t-butyl peroxide, dicumyl peroxide, t-butylcumyl peroxide, α,α'-bis(t-butylperoxy-m-isopropyl)benzene, and 2,5-di(t-butylperoxy)hexyne-3; Peroxyesters such as t-butyl peroxybenzoate, t-butyl peroxyacetate, and 2,5-dimethyl-2,5-di(benzoylperoxy)hexane; ketone peroxides such as cyclohexanone peroxide, 3,3,5-trimethylcyclohexanone peroxide, and methylcyclohexanone peroxide; Peroxyketals such as 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane, 1,1-bis(t-butylperoxy)3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclohexane, and n-butyl-4,4-bis(t-butylperoxy)valerate; Hydroperoxides such as cumene hydroperoxide, diisopropylbenzene hydroperoxide, and 2,5-dimethylcyclohexane-2,5-dihydroperoxide; diacyl peroxides such as benzoyl peroxide, decanoyl peroxide, lauroyl peroxide, and 2,4-dichlorobenzoyl peroxide; Examples include peroxydicarbonates such as bis(t-butylcyclohexyl) peroxydicarbonate.

[0050] Examples of the azo compound include 2,2'-azobisbutyronitrile such as 2,2'-azobisisobutyronitrile (ABN) and 2,2'-azobis(2-methylbutyronitrile); 2,2'-azobisvaleronitrile such as 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) and 2,2'-azobis(2,4-dimethylvaleronitrile); 2,2'-azobispropionitriles, such as 2,2'-azobis(2-hydroxymethylpropionitrile); Examples include 1,1'-azobis-1-alkanenitriles such as 1,1'-azobis(cyclohexane-1-carbonitrile).

[0051] The polymerization initiator is preferably used in an amount of 0.01 to 10 parts by mass, more preferably 0.1 to 2 parts by mass, based on 100 parts by mass of the monomer mixture.

[0052] A thiol-based chain transfer agent can be used for the purpose of adjusting the molecular weight of the copolymer (A). The thiol chain transfer agents include mercaptopropionic acid, 2-ethylhexyl-3-mercaptopropionate, stearyl-3-mercaptopropionate, thioglycerol hexanedithiol, decanedithiol, 1,4-butanediol bisthiopropionate, 1,4-butanediol bisthioglycolate, ethylene glycol bisthioglycolate, ethylene glycol bisthiopropionate, trimethylolpropane tristhioglycol ... Examples of suitable mercaptothiol esters include trimethylolpropane tris(3-mercaptobutyrate), pentaerythritol tetrakisthioglycolate, pentaerythritol tetrakisthiopropionate, trimercaptopropionic acid tris(2-hydroxyethyl)isocyanurate, 1,4-dimethylmercaptobenzene, 2,4,6-trimercapto-s-triazine, and 2-(N,N-dibutylamino)-4,6-dimercapto-s-triazine.

[0053] [Weight average molecular weight (Mw)] The weight average molecular weight of the copolymer (A) is preferably 20,000 to 1,500,000, more preferably 20,000 to 1,200,000. If it is in the range of 20,000 to 1,500,000, the cohesive force is improved, and the wet heat resistance and heat resistance are improved. The weight average molecular weight is a value measured by gel permeation chromatography (GPC) in terms of polystyrene. Details will be described in the Examples section.

[0054] <Polyfunctional (meth)acrylate monomer (B)> The polyfunctional (meth)acrylate monomer is a monomer having two or more (meth)acryloyl groups in the molecule, and examples thereof include a bifunctional (meth)acrylate monomer having two (meth)acryloyl groups in the molecule, a trifunctional (meth)acrylate monomer having three (meth)acryloyl groups in the molecule, and a polyfunctional (meth)acrylate monomer having four or more (meth)acryloyl groups in the molecule.

[0055] Specific examples of the bifunctional (meth)acrylate monomer include aliphatic (meth)acrylate monomers such as 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, and neopentyl glycol di(meth)acrylate; Aliphatic cyclic (meth)acrylate monomers such as dicyclopentanyl di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, dimethylol-tricyclodecane di(meth)acrylate, cyclohexane dimethanol di(meth)acrylate, and tricyclodecane dimethanol dimethacrylate; Aromatic (meth)acrylate monomers such as 2,2-bis(4-(meth)acryloxypropoxyphenyl)propane, 2,2-bis(4-(meth)acryloxytetraethoxyphenyl)propane, bisphenol AEO-modified di(meth)acrylate, and bisphenol FEO-modified di(meth)acrylate; Alkylene oxide-modified (meth)acrylate monomers such as dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate (200), polypropylene glycol di(meth)acrylate (400), polypropylene glycol di(meth)acrylate (700), diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate (200), polyethylene glycol di(meth)acrylate (300), polyethylene glycol di(meth)acrylate (400), and polyethylene glycol di(meth)acrylate (600); Examples of the isocyanuric acid-modified (meth)acrylate include isocyanuric acid ethylene oxide-modified di(meth)acrylate and isocyanuric acid propylene oxide-modified di(meth)acrylate.

[0056] Specific examples of the trifunctional (meth)acrylate monomer include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane EO-modified tri(meth)acrylate, trimethylolpropane PO-modified tri(meth)acrylate, isocyanuric acid EO-modified tri(meth)acrylate, and tris[(meth)acryloyloxyethyl]isocyanurate.

[0057] Specific examples of polyfunctional (meth)acrylate monomers having four or more (meth)acryloyl groups in the molecule include dimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol ethoxy tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.

[0058] Among these, from the viewpoint of achieving both cohesiveness and adhesiveness, bifunctional (meth)acrylate monomers and trifunctional (meth)acrylate monomers are preferred. Specifically, as the bifunctional (methacrylate), 1,6-hexanediol di(meth)acrylate, dicyclopentanyl di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, and polypropylene glycol di(meth)acrylate (200) are preferred, and as the trifunctional (meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane PO-modified tri(meth)acrylate, and isocyanuric acid EO-modified tri(meth)acrylate are preferred.

[0059] The polyfunctional (meth)acrylate monomer (B) is preferably contained in an amount of 1 to 40 parts by mass, more preferably 2 to 30 parts by mass, per 100 parts by mass of the acrylic copolymer (A). A content of 1 part by mass or more makes it easier to obtain sufficient cohesive strength. Also, a content of 40 parts by mass or less is preferable because it makes it easier to achieve both cohesive strength and stress relaxation properties.

[0060] These polyfunctional (meth)acrylate monomers (B) can be used alone or in combination of two or more kinds.

[0061] <Monofunctional (meth)acrylate monomer (C)> The monofunctional (meth)acrylate is a monomer having one (meth)acryloyl group in the molecule, and examples thereof include the above-mentioned monomers (a-1) to (a-4).

[0062] Among these, from the viewpoint of achieving both cohesiveness and adhesiveness, it is preferable to include at least one selected from the group consisting of aromatic (meth)acrylate monomers, aliphatic cyclic (meth)acrylate monomers, and (meth)acrylate monomers having an amide group. Specifically, it is more preferable to include at least one selected from the group consisting of benzyl (meth)acrylate, phenoxy (meth)acrylate, and ethylene oxide-modified phenol (meth)acrylate, which are aromatic (meth)acrylate monomers, isobornyl (meth)acrylate and cyclohexyl (meth)acrylate, which are aliphatic cyclic (meth)acrylate monomers, and N-hydroxyethylacrylamide, diacetoneacrylamide, and acryloylmorpholine, which are (meth)acrylate monomers having an amide group.

[0063] The monofunctional (meth)acrylate monomer (C) is preferably contained in an amount of 1 to 60 parts by mass, more preferably 2 to 50 parts by mass, based on 100 parts by mass of the acrylic copolymer (A). When the content is 1 part by mass or more, sufficient flexibility is easily obtained. Also, when the content is 60 parts by mass or less, it is preferable because it is easy to achieve both cohesive strength and stress relaxation properties.

[0064] These monofunctional (meth)acrylate monomers (C) can be used alone or in combination of two or more kinds.

[0065] <Organic peroxide (D)> The organic peroxide (D) means a compound having a peroxide structure "-OO-" in its molecular structure, and is not particularly limited, and known peroxides can be used. From the viewpoints of productivity and stability, the organic peroxide (D) used in the present invention is preferably one having a 1-minute half-life temperature of 90 to 135°C, and more preferably 100 to 135°C.

[0066] The "half-life of an organic peroxide" is an index showing the decomposition rate of an organic peroxide, and means the time until the remaining amount of the organic peroxide is reduced to half. The decomposition temperature for obtaining a half-life in a certain time and the half-life time at a certain temperature are described in manufacturer catalogs, for example, in the 10th edition of the Organic Peroxide Catalog (February 2015) published by NOF Corporation. The one-minute half-life temperature is the temperature at which the remaining amount of the organic peroxide is reduced to half in one minute.

[0067] Examples of such organic peroxides (D) are given below. The organic peroxides (D) may be either synthetic or commercially available. The temperatures in parentheses indicate the one-minute half-life temperatures. Diisopropyl peroxydicarbonate (88.3°C), di(2-ethylhexyl) peroxydicarbonate (90.6°C), di(4-t-butylcyclohexyl) peroxydicarbonate (92.1°C), di-sec-butyl peroxydicarbonate (92.4°C), t-butyl peroxyneodecanoate (103.5°C), t-hexyl peroxypivalate (109.1°C), t-butyl peroxypivalate (110.3°C), Dilauryl peroxide (116.4°C), bis-n-octanoyl peroxide (117.4°C), 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate (124.3°C), di(4-methylbenzoyl) peroxide (128.2°C), dibenzoyl peroxide (benzoyl peroxide) (130.0°C), trade names of NOF Corporation: "Perloyl IB" (85.1°C), "Perkmyl ND" (94.0°C), "Perloyl N PP (94.0℃), "Perloyl IPP" (88.3℃), "Perloyl SBP" (92.4℃), "Perocta ND" (92.4℃), "Perloyl TCP" (92.1℃), "Perloyl OPP" (90.6℃), "Perhexyl ND" (100.9℃), "Perbutyl ND" (103.5℃), "Perbutyl NHP" (104.6℃), "Perhexyl PV" (109.1℃), "Perbutyl PV" (110.3℃), "Perbutyl O" ( 134.0℃), "Perloil 355" (112.6℃), "Perloil L" (116.4℃), "Perocta O" (124.3℃), "Perloil SA" (131.8℃), "Perhexa 25O" (118.8℃), "Niper) PMB" (128.2℃), "Niper BMT" (131.1℃), "Niper BW" (130.0℃), "Niper BMT-K40" (131.1℃), "Niper BMT-M" (131.1℃), and others.

[0068] Among these, Perocta ND, Perloyl TCP, Perloyl L, and Perbutyl O are preferred from the viewpoint of achieving both stability and curability.

[0069] The organic peroxide (D) is preferably contained in an amount of 0.5 to 3 parts by mass, more preferably 1 to 2.5 parts by mass, based on 100 parts by mass of the total of the acrylic copolymer (A), the polyfunctional (meth)acrylate monomer (B) and the monofunctional (meth)acrylate monomer (C). When the content is 0.5 parts by mass or more, sufficient curability is easily obtained. Also, when the content is 3 parts by mass or less, it is preferable because it is easy to achieve both curability and stability.

[0070] These organic peroxides (D) can be used alone or in combination of two or more kinds.

[0071] <Reducing Agent (E)> The reducing agent (E) forms a redox catalyst system together with the organic peroxide (D) and can efficiently generate radicals even at room temperature. The reducing agent (E) includes at least one selected from the group consisting of tertiary amines, thiourea derivatives, and transition metal salts.

[0072] Specific examples of tertiary amines include triethylamine, tripropylamine, tributylamine, dimethylaniline, N,N-dimethyl-p-toluidine, and diazabicycloundecene.

[0073] Specific examples of the thiourea derivative include ethylenethiourea, diethylthiourea, tetramethylthiourea, monoacetylthiourea, monobenzoylthiourea, diphenylthiourea, and dicyclohexylthiourea.

[0074] Specific examples of transition metal salts include cobalt naphthenate, copper acetylacetonate, copper naphthenate, copper chloride, copper acetate, copper naphthenate, iron acetylacetonate, vanadium acetylacetonate, vanadyl acetylacetonate, vanadyl stearate, vanadium naphthenate, vanadium benzoylacetonate, and vanadium pentoxide.

[0075] Among these, from the viewpoints of solubility and reactivity, transition metal salts are preferred, and cobalt naphthenate and vanadyl acetylacetonate are more preferred.

[0076] The reducing agent (E) is preferably contained in an amount of 0.005 to 0.5 parts by mass, more preferably 0.01 to 0.1 parts by mass, based on 100 parts by mass in total of the acrylic copolymer (A), the polyfunctional (meth)acrylate monomer (B) and the monofunctional (meth)acrylate monomer (C). When the content is 0.005 parts by mass or more, sufficient curability is easily obtained. In addition, when the content is 0.5 parts by mass or less, it is preferable because it is easy to achieve both curability and stability.

[0077] These reducing agents (E) can be used alone or in combination of two or more kinds.

[0078] <Hardening agent> The pressure-sensitive adhesive of the present invention may further contain a curing agent, which reacts with the hydroxyl groups and / or carboxyl groups of the copolymer (A) to improve the cohesive strength of the pressure-sensitive adhesive layer, and thereby improve the durability and stain resistance.

[0079] Examples of the curing agent include an isocyanate compound, an epoxy compound, an aziridine compound, and a carbodiimide compound. Among these, it is preferable to use an isocyanate compound as the curing agent since it is possible to improve adhesion and durability.

[0080] The isocyanate compound is an isocyanate having two or more isocyanate groups. The isocyanate compound is preferably, for example, an isocyanate monomer such as an aromatic polyisocyanate, an aliphatic polyisocyanate, an araliphatic polyisocyanate, or an alicyclic polyisocyanate, as well as a biuret, a nurate, or an adduct thereof.

[0081] Examples of aromatic polyisocyanates include 1,3-phenylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,4-phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-toluidine diisocyanate, 2,4,6-triisocyanate toluene, 1,3,5-triisocyanate benzene, dianisidine diisocyanate, 4,4'-diphenyl ether diisocyanate, and 4,4',4"-triphenylmethane triisocyanate.

[0082] Examples of aliphatic polyisocyanates include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (also known as HMDI), pentamethylene diisocyanate, 1,2-propylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.

[0083] Examples of the aromatic aliphatic polyisocyanate include ω,ω'-diisocyanate-1,3-dimethylbenzene, ω,ω'-diisocyanate-1,4-dimethylbenzene, ω,ω'-diisocyanate-1,4-diethylbenzene, 1,4-tetramethylxylylene diisocyanate, and 1,3-tetramethylxylylene diisocyanate.

[0084] Examples of alicyclic polyisocyanates include 3-isocyanatemethyl-3,5,5-trimethylcyclohexyl isocyanate (also known as IPDI, isophorone diisocyanate), 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), and 1,4-bis(isocyanatemethyl)cyclohexane.

[0085] The biuret form is a self-condensation product having a biuret bond formed by self-condensation of an isocyanate monomer, for example, a biuret form of hexamethylene diisocyanate.

[0086] The nurate form is a trimer of an isocyanate monomer, such as a trimer of hexamethylene diisocyanate, a trimer of isophorone diisocyanate, or a trimer of tolylene diisocyanate.

[0087] The adduct is a bifunctional or higher isocyanate compound obtained by reacting an isocyanate monomer with a bifunctional or higher low-molecular active hydrogen-containing compound. Examples of the adduct include a compound obtained by reacting trimethylolpropane with hexamethylene diisocyanate, a compound obtained by reacting trimethylolpropane with tolylene diisocyanate, a compound obtained by reacting trimethylolpropane with xylylene diisocyanate, a compound obtained by reacting trimethylolpropane with isophorone diisocyanate, and a compound obtained by reacting 1,6-hexanediol with hexamethylene diisocyanate.

[0088] The isocyanate compound is preferably a trifunctional isocyanate compound from the viewpoint of forming a sufficient crosslinked structure. The isocyanate compound is more preferably an adduct which is a reaction product between an isocyanate monomer and a trifunctional low molecular weight active hydrogen-containing compound, and a nurate. The isocyanate compound is preferably a trimethylolpropane adduct of hexamethylene diisocyanate, a nurate of hexamethylene diisocyanate, a trimethylolpropane adduct of tolylene diisocyanate, a nurate of tolylene diisocyanate, a trimethylolpropane adduct of isophorone diisocyanate, or a nurate of isophorone diisocyanate, and more preferably a trimethylolpropane adduct of hexamethylene diisocyanate, a trimethylolpropane adduct of tolylene diisocyanate, or a trimethylolpropane adduct of isophorone diisocyanate.

[0089] Examples of epoxy compounds include glycerin diglycidyl ether, 1,6-hexanediol diglycidyl ether, N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N'-diglycidylaminomethyl)cyclohexane, and N,N,N',N'-tetraglycidylaminophenylmethane.

[0090] Examples of the aziridine compound include N,N'-diphenylmethane-4,4'-bis(1-aziridinecarboxite), tris-2,4,6-(1-aziridinyl)-1,3,5-triazine, and 4,4'-bis(ethyleneiminocarbonylamino)diphenylmethane.

[0091] The carbodiimide compound is preferably a high molecular weight polycarbodiimide produced by decarboxylation condensation of a diisocyanate compound in the presence of a carbodiimide catalyst. The commercially available high molecular weight polycarbodiimide is preferably the Carbodilite series from Nisshinbo Industries, Ltd. Among them, Carbodilite V-03, 07, and 09 are preferred because of their excellent compatibility with organic solvents.

[0092] The curing agent is preferably contained in an amount of 0.02 to 4.0 parts by mass, more preferably 0.04 to 1.0 part by mass, based on 100 parts by mass of the copolymer (A). When the content is 0.02 parts by mass or more, the cohesive strength is further improved, and when the content is 4.0 parts by mass or less, it is preferable that both the cohesive strength and the flexibility are easily achieved.

[0093] <Organosilane compounds> The pressure-sensitive adhesive of the present invention may further contain an organosilane compound. By using an organosilane compound, adhesion to an adherend can be imparted and durability can be improved. Examples of the organic silane compound include alkoxysilane compounds having a (meth)acryloxy group, such as 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropyltripropoxysilane, 3-(meth)acryloxypropyltributoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, and 3-(meth)acryloxypropylmethyldiethoxysilane; Alkoxysilane compounds having a vinyl group, such as vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriisopropoxysilane, vinyltributoxysilane, vinylmethyldimethoxysilane, and vinylmethyldiethoxysilane; alkoxysilane compounds having an amino group, such as 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltripropoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, and N-phenyl-3-aminopropyltrimethoxysilane; alkoxysilane compounds having a mercapto group, such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropyltripropoxysilane, 3-mercaptopropylmethyldimethoxysilane, and 3-mercaptopropylmethyldiethoxysilane; alkoxysilane compounds having an epoxy group, such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropyltripropoxysilane, 3-glycidoxypropyltributoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; tetraalkoxysilane compounds such as tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetrabutoxysilane; Examples of the silane include 3-chloropropyltrimethoxysilane, n-hexyltrimethoxysilane, n-hexyltriethoxysilane, n-decyltrimethoxysilane, n-decyltriethoxysilane, styryltrimethoxysilane, phenyltrimethoxysilane, diphenyldimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, 1,3,5-tris(3-trimethoxysilylpropyl)isocyanurate, 3-isocyanatepropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, hexamethyldisilazane, and silicone resins having alkoxysilyl groups in the molecule.

[0094] The organosilane compound is preferably used in an amount of 0.01 to 2.0 parts by mass, more preferably 0.05 to 1.0 part by mass, based on 100 parts by mass of the copolymer (A).

[0095] The pressure-sensitive adhesive of the present invention may contain various resins, oils, softeners, dyes, pigments, antioxidants, UV absorbers, weather stabilizers, plasticizers, fillers, antioxidants, antistatic agents, and the like as optional components, so long as the problem can be solved.

[0096] <Adhesive properties> The pressure-sensitive adhesive of the present invention preferably satisfies all of the following (1) to (3). (1) The storage modulus of the adhesive at 0°C and 1 Hz is 1×10 5 ~1×10 6 Pa (2) The storage modulus of the adhesive at 150°C and 1 Hz is 1×10 4 ~1×10 5 Pa (3) The peak top temperature of the loss factor of the adhesive at 1 Hz is -45 to -10°C.

[0097] <Storage modulus and loss factor> The storage modulus and loss factor of the adhesive are determined by viscoelasticity measurement at a frequency of 1 Hz. The storage modulus corresponds to the energy stored as elastic energy when the material is deformed, and is an index of the degree of hardness. In other words, the higher the storage modulus value, the harder the adhesive is, and the lower the storage modulus value, the softer it is. The loss factor is the value obtained by dividing the loss modulus, which corresponds to the energy diffused to the outside as loss energy when the material is deformed, by the storage modulus, and indicates the highest stress relaxation property in the temperature range showing the maximum value (peak top). Details of the measurement method are described in the Examples section.

[0098] The pressure-sensitive adhesive of the present invention has a storage modulus at 0° C. and 1 Hz (hereinafter sometimes abbreviated as G′(0)) of 1×10 5 ~1×10 6 Pa is preferred, and 1×10 5 ~8×10 5 It is more preferable that G'(0) is 1×10 Pa. 5 When G'(0) is 1×10 Pa or more, the stiffness in a low temperature environment is improved, and the flexibility and windability are improved. 6 When the viscosity is less than or equal to 1 Pa, the adhesiveness is improved, and the flexibility and windability are improved.

[0099] The pressure-sensitive adhesive of the present invention has a storage modulus at 150° C. and 1 Hz (hereinafter sometimes abbreviated as G′(150)) of 1×10 4 ~1×10 5 Pa is preferred, and 1×10 4 ~8×10 5 It is more preferable that G'(150) is 1×10 Pa. 4 When the G'(150) is 1×10 Pa or more, the heat resistance and processability are improved. 5 When it is equal to or less than Pa, the adhesive strength is improved.

[0100] Furthermore, the pressure-sensitive adhesive of the present invention preferably has a loss factor peak top temperature (hereinafter sometimes abbreviated as tan δ(T)) at 1 Hz of −45 to −10° C., more preferably −40 to −10° C. When tan δ(T) is −45° C. or higher, the adhesiveness is improved, and when tan δ(T) is −10° C. or lower, the flexibility at low temperatures is improved.

[0101] The pressure-sensitive adhesive of the present invention has a storage modulus within a specific range, and thereby exhibits the flexibility required for a foldable display and the winding property required for a rollable display.

[0102] <Fast curing> During processing of the adhesive, insufficient hardness of the adhesive layer may cause problems such as coating defects during roll winding after coating, orange peel and dents during the curing process. These coating defects generally occur due to insufficient crosslinking of the adhesive, and it can be said that an adhesive having fast curing properties that can shorten the curing process is suitable for suppressing coating defects. Fast curing properties can be judged by the gel fraction at the beginning of curing after coating of the adhesive. For example, the gel fraction of an adhesive sheet aged for 3 hours in a 40°C environment, more preferably the gel fraction of an adhesive sheet aged for 1 hour in a 40°C environment is 50% or more. Details of the measurement method are described in the Examples section.

[0103] <Gel fraction> The gel fraction of the adhesive can be determined by the change in mass before and after immersing the cured adhesive in an arbitrary solvent. The gel fraction indirectly indicates the degree of crosslinking of the adhesive, and a higher gel fraction indicates a higher degree of crosslinking, and a lower gel fraction indicates a lower degree of crosslinking. A specific measurement method is described in the Examples section.

[0104] "Adhesive sheet" The pressure-sensitive adhesive sheet of the present invention is an adhesive sheet used to form an adhesive layer in a laminate consisting of a light-transmitting substrate and an adhesive layer, i.e., the pressure-sensitive adhesive sheet of the present invention is used to bond light-transmitting substrates. An example of a schematic cross-sectional view partially illustrating the pressure-sensitive adhesive sheet of the present invention is shown in Fig. 1. In Fig. 1, 1 is a pressure-sensitive adhesive layer, and 2 is a release film.

[0105] As shown in FIG. 1, the adhesive sheet of the present invention has a configuration in which release films are formed on both sides of an adhesive layer, and the adhesive layer formed between the release films is an adhesive layer formed from the adhesive of the present invention which contains an acrylic copolymer (A), a polyfunctional (meth)acrylate monomer (B), a monofunctional (meth)acrylate monomer (C), an organic peroxide (D) and a reducing agent (E).

[0106] <Release film> The release film is not particularly limited, but a transparent plastic substrate can be suitably used. Examples of the material of the transparent plastic substrate include polyesters such as polyethylene terephthalate (PET), acrylic resins such as polymethyl methacrylate (PMMA), polycarbonate, triacetyl cellulose, polysulfone, polyarylate, polycycloolefin, and other plastic materials. The plastic materials can be used alone or in combination of two or more kinds.

[0107] As the release film, among the above-mentioned transparent plastic substrates, a transparent plastic substrate having excellent heat resistance, i.e., a transparent plastic substrate in which deformation is suppressed or prevented under severe conditions such as high temperature, high temperature and high humidity, can be preferably used. As the transparent plastic substrate, a PET film or sheet is particularly preferable.

[0108] The thickness of the transparent plastic substrate is not particularly limited, and is, for example, preferably from 10 to 200 μm, and more preferably from 25 to 150 μm.

[0109] The release film may have either a single layer or multiple layers. The surface of the transparent substrate may be subjected to an appropriate surface treatment, for example, a physical treatment such as a corona discharge treatment or a plasma treatment, or a chemical treatment such as an undercoat treatment.

[0110] <Manufacturing of adhesive sheets> The pressure-sensitive adhesive sheet of the present invention can be manufactured according to a normal pressure-sensitive adhesive sheet manufacturing method. For example, the pressure-sensitive adhesive sheet can be manufactured by applying an acrylic copolymer (A), a polyfunctional (meth)acrylate monomer (B), a monofunctional (meth)acrylate monomer (C), an organic peroxide (D) and a reducing agent (E) (hereinafter, sometimes simply referred to as "pressure-sensitive adhesive") to the release-treated surface of a release film so that the thickness after application is a predetermined thickness, drying to form a pressure-sensitive adhesive layer, and attaching a release film, or by applying a pressure-sensitive adhesive to the release-treated surfaces of two release films so that the thickness after application is a predetermined thickness, drying to form two pressure-sensitive adhesive layers, and then attaching each pressure-sensitive adhesive layer. In addition, when the pressure-sensitive adhesive does not contain a volatile component such as a solvent, the drying step after applying the pressure-sensitive adhesive can be omitted.

[0111] The drying conditions can be set depending on the composition and thickness of the raw material composition, the types and amounts of the organic peroxide and curing agent, and the like, and can be, for example, 3 minutes in an atmosphere at 90 to 110°C.

[0112] The thickness of the adhesive layer is not particularly limited and is, for example, preferably 10 to 500 μm, more preferably 50 to 200 μm. When the adhesive layer has a thickness of 10 to 500 μm, sufficient cohesive strength is easily obtained, and heat resistance, moist heat resistance, flexibility, and windability can be highly achieved at the same time, which is preferable.

[0113] When applying the adhesive, a conventional coater such as a gravure roll coater, reverse roll coater, kiss roll coater, dip roll coater, bar coater, knife coater, or spray coater can be used.

[0114] The pressure-sensitive adhesive sheet may be in the form of a rolled pressure-sensitive adhesive tape by cutting the sheet to a suitable width and winding the sheet into a roll.

[0115] "Laminate" The laminate of the present invention comprises a light-transmitting substrate, a pressure-sensitive adhesive layer, and a polarizing plate, and the pressure-sensitive adhesive layer is formed using the pressure-sensitive adhesive sheet of the present invention.

[0116] The laminate of the present invention is formed from a pressure-sensitive adhesive sheet having excellent transparency, heat resistance, moist heat resistance, flexibility and windability, and is therefore excellent in transparency, heat resistance, moist heat resistance, flexibility and windability.

[0117] An example of a schematic cross-sectional view partially illustrating a laminate, which is an example of the use of the pressure-sensitive adhesive sheet of the present invention, is shown in Fig. 2. In Fig. 2, 3 is a light-transmitting substrate (cover panel), 1 is a pressure-sensitive adhesive layer, and 4 is a polarizing plate.

[0118] In the laminate shown in Fig. 2, a light-transmitting substrate (cover panel) is attached to a polarizing plate via an adhesive layer made of the adhesive of the present invention. In this manner, the adhesive sheet of the present invention can be used in a form in which a transparent adhesive layer formed from the adhesive is attached to the light-transmitting substrate (cover panel) and the polarizing plate.

[0119] The light-transmitting substrate (cover panel) is not particularly limited, but a transparent plastic substrate can be suitably used. Examples of the material of the transparent plastic substrate include acrylic resins such as polyethylene terephthalate (PET) and polymethyl methacrylate (PMMA), and plastic materials such as polycarbonate, polycycloolefin, and polyimide. The plastic materials can be used alone or in combination of two or more kinds.

[0120] As the light-transmitting substrate (cover panel), among the above-mentioned transparent plastic substrates, a transparent plastic substrate having excellent heat resistance, i.e., a transparent plastic substrate in which deformation is suppressed or prevented under severe conditions such as high temperature, high temperature and high humidity, etc. As the transparent plastic substrate, polyethylene terephthalate (PET), polycycloolefin, and polyimide are particularly suitable.

[0121] The thickness of the light-transmitting substrate (cover panel) is not particularly limited, and is, for example, preferably from 100 to 2000 μm, and more preferably from 200 to 1000 μm.

[0122] "display" The display comprises the laminate of the present invention and an optical element. The optical element is not particularly limited, and examples thereof include a liquid crystal element and an organic EL element.

[0123] The display of the present invention has a laminate excellent in transparency, heat resistance, moist heat resistance, flexibility and winding ability, and is therefore excellent in transparency, heat resistance, moist heat resistance, flexibility and winding ability.

[0124] Fig. 3 shows an example of a schematic cross-sectional view partially illustrating a display, which is an example of the use of the pressure-sensitive adhesive sheet of the present invention. In Fig. 3, 3 is a light-transmitting substrate (cover panel), 1 is a pressure-sensitive adhesive layer 1, 4 is a polarizing plate, 5 is a pressure-sensitive adhesive layer 2, 6 is a barrier layer such as silicon nitride, 7 is an organic EL layer, 8 is a support such as polyimide, and 9 is an organic EL cell. Note that the configuration of the display is not limited to that shown in Fig. 3.

[0125] In the display shown in Fig. 3, a light-transmitting substrate (cover panel) is attached to a polarizing plate via an adhesive layer (adhesive layer 1) made of the adhesive of the present invention, and is further attached to an organic EL cell via an adhesive layer for polarizing plate (adhesive layer 2). In this way, the adhesive sheet of the present invention can be used in a form in which a transparent adhesive layer formed from the adhesive is attached to a light-transmitting substrate (cover panel) and a polarizing plate, and the laminate is further attached to an organic EL cell via an adhesive layer for polarizing plate. For example, in FIG. 3, the pressure-sensitive adhesive of the present invention can be used in both pressure-sensitive adhesive layer 1 and pressure-sensitive adhesive layer 2. In general, when comparing pressure-sensitive adhesive layer 1 and pressure-sensitive adhesive layer 2, the pressure-sensitive adhesive layer has higher quality requirements, and since the pressure-sensitive adhesive of the present invention has good adhesion and bonding to the substrate, it is preferably used for pressure-sensitive adhesive layer 1. In this case, the pressure-sensitive adhesive for forming pressure-sensitive adhesive layer 2 may be the pressure-sensitive adhesive of the present invention or a conventionally known pressure-sensitive adhesive.

[0126] There are no particular limitations on the uses of the displays, but examples include OLED televisions, OLED smartphones, OLED tablets, and OLED smartwatches. EXAMPLES

[0127] Next, the present invention will be described in more detail with reference to examples, but the present invention is not limited thereto. In the examples, unless otherwise specified, "parts" means "parts by mass", "%" means "% by mass", and "RH" means relative humidity. The blending amounts in the tables are in parts by mass. Note that blanks in the tables indicate that no blending was performed. The method for measuring the weight average molecular weight of the acrylic copolymer (A) and the methods for measuring the storage modulus and loss factor of the pressure-sensitive adhesive are as follows.

[0128] <Measurement of weight average molecular weight> The weight average molecular weight (Mw) of the acrylic copolymer (A) can be measured using a GPC "LC-GPC system" manufactured by Shimadzu Corporation, and the weight average molecular weight (Mw) can be determined by conversion using polystyrene with a known molecular weight as a standard substance. Device name: Shimadzu Corporation, LC-GPC system "Prominence" Column: Four GMHXL columns manufactured by Tosoh Corporation and one HXL-H column manufactured by Tosoh Corporation were connected together. Mobile phase solvent: Tetrahydrofuran Flow rate: 1.0ml / min Column temperature: 40℃

[0129] <Measurement of storage modulus and loss factor> The storage modulus is measured by using a laminate of cured adhesive to a thickness of approximately 1.0 mm as the measurement sample and performing viscoelasticity measurements under the following conditions using a TA Instrument-Waters LLC "Discovery HR-2 (DHR-2)." From the measurement results, the storage modulus and loss factor at 0°C and 150°C can be read. (Measurement conditions) Deformation mode: Torsion Measurement frequency: 1Hz Heating rate: 10℃ / min Jig shape: Parallel plate 8.0mmφ

[0130] <Production Example of Acrylic Copolymer (A)> (Copolymer (A-1)) A reaction vessel (hereinafter simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping device, and a nitrogen inlet tube was charged with 95 parts of 2-ethylhexyl acrylate (EHA) as monomer (a-1), 1 part of 2-hydroxyethyl acrylate (HEA) as monomer (a-2), 4 parts of methyl acrylate as monomer (a-4), and 0.2 parts of 2,2'-azobisisobutyronitrile (hereinafter simply referred to as "AIBN") as an initiator, and the atmosphere in the reaction vessel was replaced with nitrogen gas. Then, the mixture was heated to 60°C while stirring under a nitrogen atmosphere to start the reaction. The reaction solution was then reacted at 60°C for 4 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain a copolymer (A-1) solution with a non-volatile content of 30%. The weight average molecular weight of the obtained copolymer (A-1) was 1.2 million.

[0131] (Copolymer (A-2~A-6, A'-1, A'-2)) Copolymers (A-2 to A-6, A'-1, A'-2) were produced in the same manner as in the production of the acrylic copolymer (A-1), except that the compositions and blending amounts (parts by mass) were changed to those shown in Tables 1 and 2.

[0132] (Copolymer (A-7)) A reaction vessel (hereinafter simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping device, and a nitrogen inlet tube was charged with 91 parts of 2-ethylhexyl acrylate (EHA) as monomer (a-1), 4 parts of 2-hydroxyethyl acrylate (HEA) as monomer (a-2), 5 parts of butyl acrylate as monomer (a-4), and 5 parts of 2-ethylhexyl-3-mercaptopropionate as a chain transfer agent, and the atmosphere in the reaction vessel was replaced with nitrogen gas. Then, the mixture was heated to 50°C while stirring under a nitrogen atmosphere. Then, 0.02 parts of AIBN was added to the reaction vessel as an initiator to start the reaction. Then, 0.02 parts of AIBN was added a total of 19 times at 15-minute intervals, and the reaction solution was reacted at 50°C for 8 hours. After the reaction was completed, the mixture was cooled to obtain a copolymer (A-7) solution with a non-volatile content of 100%. The weight average molecular weight of the resulting copolymer (A-7) was 30,000.

[0133] (Copolymer (A-8~A-10, A'-3, A'-4)) Copolymers (A-8 to A-10, A'-3, A'-4) were produced in the same manner as in the production of the acrylic copolymer (A-7), except that the compositions and blending amounts (parts by mass) were changed to those shown in Tables 1 and 2.

[0134] The weight average molecular weights (Mw) of the resulting copolymers (A-1 to 10, A'-1 to 4) are shown in Table 1.

[0135] [Table 1]

[0136] The abbreviations in the table are as follows. (Monomer (a-1)) EHA: 2-ethylhexyl acrylate (alkyl group carbon number: 8) OA: Octyl acrylate (alkyl group carbon number: 8) DOA: Dodecyl acrylate (alkyl group carbon number: 12) (Monomer (a-2)) HEA: 2-hydroxyethyl acrylate HBA: 4-hydroxybutyl acrylate (Monomer (a-3)) AA: Acrylic acid MAA: Methacrylic acid (Monomer (a-4)) MA: Methyl acrylate (alkyl group carbon number 1) BA: Butyl acrylate (alkyl group carbon number: 4)

[0137] Example 1 <Preparation of Adhesive> 100 parts of the nonvolatile content of the acrylic copolymer (A-1) was mixed with 1 part of 1,6-hexanediol diacrylate (HDDA) as the polyfunctional (meth)acrylate monomer (B), 2 parts of N-hydroxyethylacrylamide (HEAA) as the monofunctional (meth)acrylate monomer (C), 1 part of perbutyl O (PBO) as the organic peroxide (D), and 0.005 parts of diazabicycloundecene (DBU) as a reducing agent, and stirred to obtain an adhesive.

[0138] <Manufacturing of adhesive sheets> The obtained adhesive was applied onto a 50 μm-thick release film (polyethylene terephthalate (PET), "E7004", silicone-based release layer, manufactured by Toyobo Co., Ltd.) so that the thickness after drying would be 50 μm, and the coating was dried at 100° C. for 3 minutes to form an adhesive layer. Next, one side of a 38 μm-thick release film (polyethylene terephthalate, "SP-PET3811", silicone-based release layer, manufactured by Lintec Corporation) was bonded to this adhesive layer to produce a "release sheet / adhesive layer / release sheet" laminate. Next, the obtained laminate was aged in a 40° C. environment for 3 days to obtain an adhesive sheet.

[0139] (Examples 2 to 6, Examples 11 to 13, Comparative Examples 1, 2, 5 to 9, 13 to 16) As shown in Tables 2 and 3, pressure-sensitive adhesive sheets were obtained in the same manner as in Example 1, except that the types and amounts (parts by mass) of copolymer and curing agent were changed.

[0140] Example 7 <Preparation of Adhesive> For 100 parts of the nonvolatile content of the acrylic copolymer (A-7), 40 parts of trimethylolpropane PO modified triacrylate (TMPPOTA) as the multifunctional (meth)acrylate monomer (B), 40 parts of 2-ethylhexyl acrylate (EHA) as the monofunctional (meth)acrylate monomer (C), 1 part of Perloyl L (PLL) as the organic peroxide (D), 0.02 parts of cobalt naphthenate (NC) as a reducing agent, and 3-glycidoxypropyltrimethoxysilane (GPTMS) as a silane compound were mixed and stirred to obtain an adhesive.

[0141] <Manufacturing of adhesive sheets> The obtained adhesive was applied onto a 50 μm-thick release film (polyethylene terephthalate (PET), "E7004", silicone-based release layer, manufactured by Toyobo Co., Ltd.) so that the thickness after application was 50 μm, forming an adhesive layer. Next, one side of a 38 μm-thick release film (polyethylene terephthalate, "SP-PET3811", silicone-based release layer, manufactured by Lintec Corporation) was attached to this adhesive layer to produce a "release sheet / adhesive layer / release sheet" laminate. Next, the obtained laminate was aged in a 40° C. environment for 3 days to obtain an adhesive sheet.

[0142] (Examples 8 to 10, Examples 14 to 16, Comparative Examples 3, 4, 10 to 12) As shown in Tables 2 and 3, pressure-sensitive adhesive sheets were obtained in the same manner as in Example 7, except that the types and amounts (parts by mass) of the copolymer and curing agent were changed.

[0143] [Table 2]

[0144] [Table 3]

[0145] The abbreviations in the table are as follows. <Polyfunctional (meth)acrylate (B)> HDDA: 1,6-Hexanediol diacrylate DCPDA: dicyclopentanyl diacrylate DPGDA: Dipropylene glycol diacrylate TPGDA: Tripropylene glycol diacrylate PPGDA: Polypropylene glycol diacrylate (200) TMPTA: Trimethylolpropane triacrylate TMPPOTA: Trimethylolpropane PO modified triacrylate INEOTA: Isocyanuric acid EO modified triacrylate <Monofunctional (meth)acrylate (C)> EHA: 2-Ethylhexyl acrylate BzA: benzyl acrylate PEA: Phenoxyacrylate EOPA: Ethylene oxide modified phenol acrylate (M112) IBXA: Isobornyl acrylate CHA: Cyclohexyl acrylate DAAM: Diacetone acrylamide HEAA: N-hydroxyethylacrylamide ACMO: Acryloylmorpholine <Organic peroxide (D)> PBO: Perbutyl O (NOF Corporation, 1-minute half-life temperature 134.0°C) POND: Perocta ND (NOF Corporation, 1-minute half-life temperature 92.4°C) PLTCP: Perloyl TCP (NOF Corporation, 1-minute half-life temperature 92.1°C) PLL: Perloil L (NOF Corporation, 1-minute half-life temperature 116.4°C) <Organic peroxide (D')> PLIB: Perloil IB (NOF Corporation, 1-minute half-life temperature 85.1°C) PHHC: Perhexa HC (NOF Corporation, 1-minute half-life temperature 149.2°C) <Reducing Agent (E)> DBU: Diazabicycloundecene DPTU: Diphenylthiourea NC: Cobalt naphthenate VA: Vanadyl acetylacetonate <Reducing Agent (E')> ADH: adipic acid dihydrazide <Hardening agent> TDITMP: Trimethylolpropane adduct of tolylene diisocyanate TGXDA: N,N,N',N'-tetraglycidyl-m-xylylenediamine <Organosilane compounds> GPTMS: 3-glycidoxypropyltrimethoxysilane

[0146] <Measurement and evaluation of physical properties of adhesive sheets> The obtained adhesive sheet was used to evaluate the storage modulus, loss factor, and the following properties: fast curing property, gel fraction, transparency, heat resistance, moist heat resistance, dynamic bending resistance, static bending property, and winding property. Fast curing property was evaluated using an adhesive sheet that had been aged for 3 hours in a 40°C environment. The results are shown in Tables 2, 3, and 4.

[0147] <Gel fraction and fast curing> The obtained adhesive sheet was cut into a size of 25 mm wide x 100 mm long. One release film of the cut adhesive sheet was peeled off, and the sheet was attached to a 200 mesh of 50 mm wide x 120 mm long, whose mass had been measured in advance. Next, the other release film was peeled off, and the mesh was folded so that the adhesive was on the inside so that the adhesive was not exposed. The adhesive wrapped in the mesh was immersed in about 50 mL of ethyl acetate at 50 ° C for 1 day, and the sol component of the adhesive was dissolved out of the mesh. After immersion, the adhesive wrapped in the mesh was taken out, dried at 100 ° C for 1 hour, and allowed to cool for about 20 minutes, and then the dry mass was measured. The gel fraction of the adhesive was calculated by the following formula. Gel fraction (mass%) = (Y / X) x 100 X = mass of adhesive layer before immersion (g) Y = mass of adhesive layer after immersion (g) In addition, the gel fraction of the pressure-sensitive adhesive sheet that had been aged in a 40° C. environment for 3 hours was measured according to the above-mentioned measurement method, and the rapid curing property was evaluated according to the following criteria. ○: Gel fraction is 50% or more (good). ×: Gel fraction is less than 50% (poor).

[0148] <Preparation of test adhesive sheets> The 38 μm-thick release film was peeled off from the obtained adhesive sheet, and the exposed adhesive layer was attached to a 50 μm-thick PET film (T60, manufactured by Toray Industries, Inc.) using a laminator at 23°C and 50% RH to produce a test adhesive sheet consisting of PET film / adhesive layer / release film.

[0149] <Transparency> The test adhesive sheet was cut to a size of 112 mm wide x 200 mm long (equivalent to a 9-inch display). The release film was peeled off from the cut test adhesive sheet, and the exposed adhesive layer was attached to an alkali-free glass plate (EN-A1: manufactured by Asahi Glass Co., Ltd.) using a laminator in an atmosphere of 25°C and 50% RH, and the haze was measured. The haze was measured using a Turbidimeter NDH5000W manufactured by Nippon Denshoku Industries Co., Ltd. The evaluation criteria are as follows: [Evaluation Criteria] ○: Haze is less than 1.0 (good). ×: Haze is 1.0 or more (poor).

[0150] <Heat resistance / humid heat resistance> The release film was peeled off from a test adhesive sheet prepared separately, and the exposed adhesive layer was attached to a polarizing plate (layer structure: triacetyl cellulose film / polyvinyl alcohol film / cycloolefin film) using a laminator in an atmosphere of 25°C and 50% RH to obtain a test laminate consisting of a PET film / adhesive layer / polarizing plate. Next, as a heat resistance test, the laminate was left for 500 hours under a condition of 105°C, and cooled in an atmosphere of 25°C and 50% RH, and then the generation of bubbles and the lifting and peeling of the test laminate were visually evaluated under the following conditions. In addition, as an evaluation of moist heat resistance, the above test laminate was left for 500 hours in an atmosphere of 60°C and 95% RH, and then cooled in an atmosphere of 25°C and 50% RH, and then the generation of bubbles and the lifting and peeling of the adhesive sheet were visually evaluated under the following conditions. Heat resistance and moist heat resistance were evaluated based on the following three-stage evaluation criteria. [Evaluation Criteria] ⊚: No air bubbles, floating or peeling were observed, and there were no problems in practical use. ◯: Air bubbles, lifting, or peeling was observed in less than five places, but this did not cause any problems in practical use. ×: Air bubbles, floating or peeling were observed in 5 or more places, and the product was problematic for practical use.

[0151] <Dynamic flex resistance: flex resistance [1], [2], [3]> The release film was peeled off from a separately prepared test adhesive sheet, and the exposed adhesive layer was attached to a polarizing plate (layer structure: triacetyl cellulose film / polyvinyl alcohol film / cycloolefin film) using a laminator at 25°C and 50% RH to obtain a test laminate consisting of a PET film / adhesive layer / polarizing plate. Next, the test laminate was subjected to a normal test of bending resistance at 25°C and 50% RH [1], a heat resistance test of bending resistance at 85°C [2], and a moist heat resistance test of bending resistance at 60°C and 95% RH [3], using a bending tester (manufactured by Yuasa System Co., Ltd.) with the PET side of the test piece facing inward, and the conditions were set so that the inner diameter (diameter) when folded was 6 mm, and folding and opening at 180° were repeated 300,000 times as one cycle. The dynamic bending property was evaluated by the appearance after the test from the following viewpoints. Appearance: The test laminate was visually inspected for the presence or absence of air bubbles and the presence or absence of lifting or peeling of the adhesive layer under the following conditions. [Evaluation Criteria] ⊚: No air bubbles, floating or peeling were observed, and there were no problems in practical use. ◯: Air bubbles, lifting, or peeling was observed in less than five places, but this did not cause any problems in practical use. ×: Air bubbles, floating or peeling were observed in 5 or more places, and the product was problematic for practical use.

[0152] <Static bending resistance: Flexing resistance [1], [2], [3]> The release film was peeled off from a separately prepared test adhesive sheet, and the exposed adhesive layer was attached to a polarizing plate (layer structure: triacetyl cellulose film / polyvinyl alcohol film / cycloolefin film) using a laminator at 25°C and 50% RH to obtain a test laminate consisting of a PET film / adhesive layer / polarizing plate. Next, the test laminate was subjected to bending resistance [1] at 25°C and 50% RH as a normal test, bending resistance [2] at 85°C as a heat resistance test, and bending resistance [3] at 60°C and 95% RH as a moist heat resistance test, each of which was held in a bent state with a bending radius of 3 mm and a bending angle of 180° for 240 hours using a planar body no-load U-shaped stretch tester with the PET side of the test piece facing inward. The static bending resistance was evaluated based on the appearance after the test from the following perspectives. Appearance: The test laminate was visually inspected for the presence or absence of air bubbles and the presence or absence of lifting or peeling of the adhesive layer under the following conditions. [Evaluation Criteria] ⊚: No air bubbles, floating or peeling were observed, and there were no problems in practical use. ◯: Air bubbles, lifting, or peeling was observed in less than five places, but this did not cause any problems in practical use. ×: Air bubbles, floating or peeling were observed in 5 or more places, and the product was problematic for practical use.

[0153] <Windability> The release film was peeled off from a test adhesive sheet prepared separately, and the exposed adhesive layer was attached to a polarizing plate (layer structure: triacetyl cellulose film / polyvinyl alcohol film / cycloolefin film) using a laminator in an atmosphere of 25°C and 50% RH to obtain a test laminate consisting of a PET film / adhesive layer / polarizing plate. Next, the test laminate was wound up in the long direction around a metal rod with a radius of 3 mm, with the PET side of the test piece facing inward, and then rolled up, and then tied and fixed at three places with a string. For the winding test, the rolled test laminate was kept in an atmosphere of 25°C and 50% RH for 240 hours. The winding property was evaluated based on the appearance after the test from the following viewpoints. Appearance: The test laminate was visually inspected for the presence or absence of air bubbles and the presence or absence of lifting or peeling of the adhesive layer under the following conditions. [Evaluation Criteria] ⊚: No air bubbles, floating or peeling were observed, and there were no problems in practical use. ◯: Air bubbles, lifting, or peeling was observed in less than five places, but this did not cause any problems in practical use. ×: Air bubbles, floating or peeling were observed in 5 or more places, and the product was problematic for practical use.

[0154] [Table 4]

[0155] The abbreviations in the table are as follows. Layer structure of test pressure-sensitive adhesive sheet and test laminate [A]: PET film / adhesive layer / glass [B]: PET film / adhesive layer / polarizing plate Test conditions Bending resistance [1]: 25°C, 50% relative humidity Bending resistance [2]; 85℃ atmosphere Bending resistance [3]: 60°C, 95% relative humidity

[0156] From the results in Table 4, it was confirmed that the pressure-sensitive adhesive sheets of Examples 1 to 16 were excellent in heat resistance, moist heat resistance, flexibility and windability in addition to transparency. As a result, the laminate and display using the pressure-sensitive adhesive sheet of the present invention are excellent in transparency, heat resistance, moist heat resistance and flexibility. Furthermore, the display of the present invention was also excellent in visibility and contrast. On the other hand, the pressure-sensitive adhesive sheets of Comparative Examples 1 to 16 could not satisfy all of the above characteristics. [Explanation of symbols]

[0157] 1 Adhesive layer 1 2 Release film 3. Light-transmitting substrate (cover panel) 4. Polarizing Plate 5 Adhesive layer 2 6 Barrier Layer 7 Organic EL layer 8 Support 9 Organic EL Cell

Claims

1. The composition comprises an acrylic copolymer (A), a polyfunctional (meth)acrylate monomer (B), a monofunctional (meth)acrylate monomer (C), an organic peroxide (D), and a reducing agent (E), The acrylic copolymer (A) is a copolymer of a monomer mixture containing a (meth)acrylic acid alkyl ester monomer (a-1) having an alkyl group with a carbon number of 8 to 12, and a monomer (a-2) having a hydroxyl group and / or a monomer (a-3) having a carboxyl group; The organic peroxide (D) has a 1-minute half-life temperature of 90 to 135° C., The reducing agent (E) includes at least one selected from the group consisting of a tertiary amine, a thiourea derivative, and a transition metal salt; The adhesive comprises 0.5 to 3 parts by mass of an organic peroxide (D) and 0.005 to 0.5 parts by mass of a reducing agent (E) relative to a total of 100 parts by mass of the acrylic copolymer (A), the polyfunctional (meth)acrylate monomer (B), and the monofunctional (meth)acrylate monomer (C).

2. The pressure-sensitive adhesive according to claim 1, characterized in that the monofunctional (meth)acrylate monomer (C) comprises at least one selected from the group consisting of aromatic (meth)acrylate monomers, aliphatic cyclic (meth)acrylate monomers, and (meth)acrylate monomers having an amide group.

3. The pressure-sensitive adhesive according to claim 1, comprising 1 to 40 parts by mass of a polyfunctional (meth)acrylate monomer (B) and 1 to 60 parts by mass of a monofunctional (meth)acrylate monomer (C) relative to 100 parts by mass of the acrylic copolymer (A).

4. The pressure-sensitive adhesive according to claim 1, which satisfies all of the following (1) to (3): (1) The storage modulus of the adhesive at 0° C. and 1 Hz is 1×10 5 ~1×10 6 P (2) The storage modulus of the adhesive at 150° C. and 1 Hz is 1×10 4 ~1×10 5 P (3) The peak top temperature of the loss factor of the adhesive at 1 Hz is -45 to -10°C.

5. 5. A pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer, the pressure-sensitive adhesive layer being a cured product of the pressure-sensitive adhesive according to claim 1, sandwiched between release films.

6. 5. A laminate comprising a light-transmitting substrate, a pressure-sensitive adhesive layer, and a polarizing plate, the pressure-sensitive adhesive layer being a cured product of the pressure-sensitive adhesive according to claim 1.

7. A display comprising the laminate according to claim 6 and an optical element.

Citation Information

Patent Citations

  • Optical adhesive sheet

    JP2023047037A

  • Active energy ray-curable adhesive composition, cured product, and adhesive sheet

    JP2023070690A